Analyses of clinical and histopathological characteristics of twelve cases of cutaneous Mycobacterium marinum infections - Lu YANG; Jianjian LI; Ting LIU; Han MA; Yanqing CHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To analyze the clinical manifestations and histopathological features of cutaneous Mycobacterium marinum infections in order to improve the understanding, diagnosis and treatment of this disease. Methods We retrospectively analyzed the clinical manifestations, histopathological features, treatment and outcome of 12 cases of cutaneous Mycobacterium marinum infections diagnosed at the Fifth Affiliated Hospital of Sun Yat-Sen University from 2020 to 2023. Results The average age was 47.3 years. Seafood-induced trauma was a risk factor. Clinical presentations often included unilateral distribution of multiple chronic nodules and plaques on the upper limb, resembling sporotrichosis. Pathological findings included epidermal acanthosis, dermal non-specific inflammatory infiltration, and sometimes with tuberculosis-like granulomas. However, the positive rate of acid-fast staining was low. Nine patients received anti-infective therapy consisting of clarithromycin combined with rifampicin or moxifloxacin. The treatment regimen for other three patients was unknown. All patients experienced resolution of their skin lesions without serious adverse drug reactions, and there were no recurrences during 1-year follow-up. Conclusions Mycobacterium marinum infection should be suspected in patients, especially middle-aged and elderly individuals with a history of trauma or handling seafood, presenting with chronic nodules and plaques, along with pathological findings of tuberculosis-like granuloma or non-specific inflammatory infiltration. These patients can be treated with clarithromycin and rifampicin.